2004
DOI: 10.31729/jnma.491
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use among Women in a Town of Eastern Nepal

Abstract: A community-based cross-sectional survey with cluster sampling method (probability proportionate to size) was carried out to estimate the prevalence of alcohol consumption among Nepalese women in Dharan town to assess the pattern of use and to identify the factors associated with this habit. A representative sample of 2340 women, aged 15 years and above was interviewed in 2002. The estimated prevalence of alcohol consumption was nearly 17%. Alcohol use is prevalent among females of hill ethnic groups. Nearly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 14 publications
5
23
0
Order By: Relevance
“…8,10,12,14,15. Considering their religion, our study showed preponderance of Hindus and is comparable to one similar study given the main religion followed in Nepal. 10 Ethnicity wise, our study showed preponderance of Brahmins while other studies had varying results; Khetriya 4 ,and Rai 14 . Occupation wise, majority of the patients were involved in some kind of business or service in our study and results were comparable to other studies.…”
Section: Discussionmentioning
confidence: 51%
“…8,10,12,14,15. Considering their religion, our study showed preponderance of Hindus and is comparable to one similar study given the main religion followed in Nepal. 10 Ethnicity wise, our study showed preponderance of Brahmins while other studies had varying results; Khetriya 4 ,and Rai 14 . Occupation wise, majority of the patients were involved in some kind of business or service in our study and results were comparable to other studies.…”
Section: Discussionmentioning
confidence: 51%
“…The prevalence of alcohol consumption was 48.1% among female in present study which is higher than 16.6% the findings of study conducted by Niraula et al at Sunsari. 11 This marked difference in prevalence may be due to study area in the present study high majority of ethnic groups Majhi/ Danuwar where alcohol is used traditionally. In the present study, the mean age of initiating drinking alcohol was found to be 16.7 years.…”
Section: Discussionmentioning
confidence: 63%
“…15 Few studies from eastern Nepal reported a prevalence of smoking among females as 15.4% and 12.9%. 16,17 In the USA and other developed countries, tobacco smoking has been found to be an important risk factor in the development of bronchogenic carcinoma. 18 In the present study, 17% of patients of bronchogenic carcinoma were non-smokers.…”
Section: Discussionmentioning
confidence: 99%